2016
DOI: 10.1111/1750-3841.13262
|View full text |Cite
|
Sign up to set email alerts
|

The Quality Changes of Postharvest Mulberry Fruit Treated by Chitosan‐g‐Caffeic Acid during Cold Storage

Abstract: This study aimed to characterize the effects of chitosan-g-caffeic acid (CTS-g-CA) on improving the quality and extending the shelf life of postharvest mulberry fruit during storage at 4 °C for 18 d. CTS-g-CA was enzymatically synthesized using laccase from Pleurotus ostreatus as a catalyst. The synergistic effects of CTS-g-CA treatment on mulberry fruit were evaluated using a co-toxicity factor (cf). The results showed that the rotting rate of CTS-g-CA-treated fruit was 37.67% (compared with that of the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Mulberry fruits of Dashi (M. alba Lin.) were collected at 90% commercial maturity in Zhenjiang, Jiangsu Province (Yang et al, 2016). The fruits with uniform size, color and absence of visual damages were chosen for the experiments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mulberry fruits of Dashi (M. alba Lin.) were collected at 90% commercial maturity in Zhenjiang, Jiangsu Province (Yang et al, 2016). The fruits with uniform size, color and absence of visual damages were chosen for the experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Mulberry is a soft fruit and easily to decay by mechanics and microbe factors (Yang et al, 2016). The mulberry fruits treated with 0.20 g/L caffeic acid had a significantly (P < 0.05) lower weight loss compared with the control (Figure 1).…”
Section: Effects Of Caffeic Acid On Ld 90 Of the Mulberry Fruits Stormentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, the reaction has the advantages of good regioselectivity and environmental friendliness. It has been reported that galactose [82], curcumin [35], inulin [83], and caffeic acid [84] can be successfully coupled with chitosan to obtain the corresponding conjugates by this method. It should be noted that, considering the instability of the Schiff base, the chitosan Schiff base conjugate is usually reduced to a stable amino-substituted chitosan conjugate through sodium borohydride or sodium cyanoborohydride [37,85,86].…”
Section: Coupling By Forming a Schiff Basementioning
confidence: 99%
“…Treatment with 1‐MCP alone could not prevent a decline in ascorbic acid levels and in the sensory quality of the mulberries, and treatment with CaCl 2 alone could control the degree of reduction in ascorbic acid levels and the browning rate of mulberries. Ozone (Han et al, ; Tabakoglu & Karaca ), chitosan‐g‐caffeic acid (CTS‐g‐CA) (Yang, Han, & Zheng, & Y., Liu, L., ), and calcium oxide (CaO) (Yang & Youngeon ) treatments were also found to have significant effects on maintaining the quality of mulberries. However, their use is limited due to their low efficacies and instability.…”
Section: Introductionmentioning
confidence: 99%